1999
DOI: 10.1038/sj.onc.1202601
|View full text |Cite
|
Sign up to set email alerts
|

DEF-3(g16/NY-LU-12), an RNA binding protein from the 3p21.3 homozygous deletion region in SCLC

Abstract: DEF-3(g16/NY-LU-12) encodes a novel RNA binding protein isolated by positional cloning from an SCLC homozygous deletion region in 3p21.3 and, in parallel, as a dierentially expressed gene during myelopoiesis from FDCPmix-A4 cells. DEF-3(g16/NY-LU-12) is ubiquitously expressed during mouse embryogenesis and in adult organs while human hematopoietic tissues showed dierential expression. The mouse and human proteins are highly conserved containing two RNA recognition motifs (RRMs) and other domains associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…This finding, although it needs to be validated by actual experiments, such as a gel-shift assay, is in a good correlation with the previous observations that the H37 protein contains RNA-binding motifs (i.e., RBM5 is another name for H37/Luca15; refs. 15,32), and H37 shows in vitro RNA-binding activity (33). Taken together, our current hypothesis is that H37 may function in some aspects of post-transcriptional regulations of certain important proteins involved in cell cycle and/or apoptosis (i.e., Bax, cyclin A, RB, etc.).…”
Section: Discussionmentioning
confidence: 74%
“…This finding, although it needs to be validated by actual experiments, such as a gel-shift assay, is in a good correlation with the previous observations that the H37 protein contains RNA-binding motifs (i.e., RBM5 is another name for H37/Luca15; refs. 15,32), and H37 shows in vitro RNA-binding activity (33). Taken together, our current hypothesis is that H37 may function in some aspects of post-transcriptional regulations of certain important proteins involved in cell cycle and/or apoptosis (i.e., Bax, cyclin A, RB, etc.).…”
Section: Discussionmentioning
confidence: 74%
“…RBM5 is an RNA-binding protein containing two RNA recognition motifs (26,34). However, the cellular targets for RBM5 had not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length LUCA-15 protein contains a number of functional motifs, including two RNA binding domain motifs, two putative zinc-®nger DNA binding motifs, and a nuclear localization sequence. Recent studies have demonstrated that recombinant proteins containing LUCA-15 RNA binding motifs speci®cally bind poly(G) RNA homopolymers in vitro (Drabkin et al, 1999). Assuming that the splice variants delineated in Figure 2 are all part of translated sequences, and that these have the same start site as the LUCA-15 cDNA in the databanks, any protein encoded by the alternatively spliced LUCA-15 variant containing only the Je2 intron (Figure 2civ) would retain only RNA binding domain 1 (as there is a stop codon following exon 6).…”
Section: Discussionmentioning
confidence: 99%